Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1177/193229680800200121
|View full text |Cite
|
Sign up to set email alerts
|

Computerized Learning Technologies for Diabetes: A Systematic Review

Abstract: Abbreviations: (DQOL) diabetes quality of life, (MeSH) Medical Subject HeadingsKeywords: computer-assisted instruction, diabetes mellitus, patient education, randomized controlled trials

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 31 publications
0
17
0
1
Order By: Relevance
“…Most studies evaluating dietary changes have shown positive results in self-reports, including improvement in the intake of carbohydrates and lipids and a decrease in total kcal (17)(18). Educational interventions in diabetes with a short follow-up up to 6 months tended to show greater efficacy (19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies evaluating dietary changes have shown positive results in self-reports, including improvement in the intake of carbohydrates and lipids and a decrease in total kcal (17)(18). Educational interventions in diabetes with a short follow-up up to 6 months tended to show greater efficacy (19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…39 A variety of such technologies have been identified, including those that address prevention and management of complications. 30,39 Information and computer technology may present opportunities to enhance care among populations with low health literacy. 40 Symposium participants recommended that diabetes educators consider making use of these rapidly developing technologies, especially among the population demographic for whom they are the preferred means of communication.…”
Section: Effective Interventions and Strategies To Reduce Risksmentioning
confidence: 99%
“…Digital diabetes tools have been designed for coaching people with diabetes by personalized diabetes education . Users define long‐term goals, such as losing weight, decreasing blood glucose levels, and receive daily messages to attain specific goals and to reiterate essential concepts of diabetes education.…”
Section: What Is Diabetes Education?mentioning
confidence: 99%
“…Digital diabetes tools have been designed for coaching people with diabetes by personalized diabetes education. 75 Users define long-term goals, such as losing weight, decreasing blood glucose levels, and receive daily messages to attain specific goals and to reiter- Telemedicine has been particularly helpful for people with diabetes who live in remote areas and do not have access to professional counseling and diabetes education resources. 80 The communication and exchange of medical information are made possible through videoconferencing during a telemedicine session.…”
Section: Diabetes Education and Digital Technologiesmentioning
confidence: 99%